The Impact Of BPRS Financing on The MSMEs Output Value: Panel Data Analysis Period 2017-2024 - Huzaifa, Hafiz (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: Micro, Small, and Medium Enterprises (MSMEs) are vital to the Indonesian economy, yet they face significant challenges, primarily constrained financing, with only about IDR 700 trillion of the IDR 1,700 trillion annual capital needs being met by existing financial institutions. Furthermore, a large percentage of MSMEs do not utilize bank loans or are unaware of the procedures, while those who do often perceive high interest rates as burdensome. Sharia Rural Banks (BPRS) have shown a favorable trend in finance growth, offering sharia-aligned inclusive financing. However, most prior research concentrates on financing from Islamic banks or is geographically confined, with deficiencies in correlating specific BPRS funding types with MSME output value across Indonesia.Purpose/Objective Study: This study seeks to investigate the impact of BPRS financing, specifically categorized as working capital financing, investment financing, and financing for MSMEs, on the output value of MSMEs across province in Indonesia.Design/Methodology/Approach: This explanatory research employed a quantitative approach using panel data from 22 provinces in Indonesia over the 2017-2024 period. The study utilized secondary data and the Resource-Based View Theory as a framework. The Fixed Effect Model (FEM) was selected as the most appropriate estimation method based on the Chow and Hausman tests.Findings: The analysis indicates that BPRS financing simultaneously has a positive and significant effect on MSME output value. Thus, working capital financing and financing for MSMEs has an insignificant positive impact. Conversely, investment financing shows an insignificant negative effect. The insignificant results are attributed to factors such as low Islamic financial literacy and inclusion, behavioral biases, high NPF ratios in investment, and BPRS's inefficient intermediation due to a lack of non-financial support like training and mentoring.